Sustainable Eco-Tourism in Tinjure Hills: A Spotlight on Nepal's Rhododendron Capital - Budhathoki, Drona (International Research Journal of MMC, 2024)
The main foundation of tourism development in Tinjure, a hilly district of Terhathum, is the vast blooming of rhododendrons across the hills. With 28 species of rhododendrons found in this region, the Tinjure, Milke, and Jaljale areas are known as the " Rhododendron Capital" of Nepal. Among these three areas, Tinjure is the region where the highest number of rhododendrons are found. Domestic tourists visit throughout the year, while both domestic and foreign tourists are drawn to the area during the rhododendron bloom from March to April months. This initiative aims to promote this important tourist destination globally through eco-tourism. The main objective of this study is to explore the foundations of tourism development and identify the challenges of eco-tourism in Tinjure Hills. Primary data were directly taken from the local communities through interview, and self-observation in 2024. Similarly, and books, articles, bulletin, journal, and website materials were used as a secondary data. Additionally, videos produced by Purvi Blues and Entertainment MMC were used as supplementary data to enrich the study. The Tinjure hills offer significant ecotourism potential, boasting diverse attractions, such as rhododendron forests (March-April), summer retreats, panoramic autumnal mountain views, and winter snowfall. This variety caters to broad tourist preferences while showcasing rich biodiversity. Cultural landmarks, including the iconic rhododendron and Tinjure Pathivara Temple, appeal to domestic visitors. Both domestic and international tourist numbers have been increasing annually. Infrastructure improvements support ecotourism growth. To attract international tourists, strategic planning, policy development, and research on visitor behavior and service optimization are crucial for sectoral advancement.